Measurement of Coherence Time in Cold Atom-Generated Tunable Photon Wave Packets Using an Unbalanced Fiber Interferometer - Ya Li; Wanru Wang; Qizhou Wu; Youxing Chen; Can Sun; Hai Wang; Weizhe Qiao (Photonics)
In the realm of quantum communication and photonic technologies, the extension of coherence time for photon wave packets is essential for improving system efficacy. This research introduces a methodology for measuring coherence time utilizing an unbalanced fiber interferometer, specifically designed for tunable pulse-width photon wave packets produced by cold atoms. By synchronously generating write pulses, signal light, and frequency-locking light from a single laser source, the study effectively mitigated frequency discrepancies that typically arise from the use of multiple light sources. The implementation of frequency-resolved photon counting under phase-locked conditions was accomplished through the application of polarization filtering and cascaded filtering techniques. The experimental results indicated that the periodicity of frequency shifts in interference fringe patterns diminishes as the differences in delay arm lengths increase, while fluctuations in fiber length and high-frequency laser jitter adversely affect interference visibility. Through an analysis of the correlation between delay and photon counts, the coherence time of the write laser was determined to be 2.56 µs, whereas the Stokes photons produced through interactions with cold atoms exhibited a reduced coherence time of 1.23 µs. The findings suggest that enhancements in laser bandwidth compression and fiber phase stability could further prolong the coherence time of photon wave packets generated by cold atoms, thereby providing valuable technical support for high-fidelity quantum information processing.